KEBIJAKAN PENGELOLAAN RUANG TERBUKA HIJAU PERKOTAAN (STUDI KASUS: PEMERINTAH KOTA SURABAYA) - , MONICA SINDY HERYUKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Development, urbanization, and environment pollution are three phenomena that become common problems for big cities. Cities phsycal development changes cities landscape becomes full of buildings, roads, bridges, and other pavements. It is necesary to pay sufficient attention to environment preservation in cities policy management. Green open space is a part of cities element which functions as: ecology, esthetics, social, culture, and economic. Even tough it has crucial role, it is possible that the green open space becomes targets of fulfilling the need of space in development. Therefore green open space policy management, which guarantees its existence, is badly needed. There are not many cities, which can sustain the existence of green open space. Surabaya, which is identic with its industrial affairs, trading, and service, is successful in attaining various kinds of reward in relation with living environment preservation. One of the factors Surabaya can attain this achievement is its green open space existence that its quality and quantity fit its needs. This research is intended to find out description of green open space policy management include the policy document, the process of implementation, and the role of the actors of the green open space management in Surabaya and identify what factors influence them. The method used in this research is case study because learning from Surabaya experiences can enrich the concepts of green open space management. The description of green open space policy manajemen in Surabaya indicate the factors influence them. Those can be the source of learning to other cities in green open space management.